1996
DOI: 10.1038/sc.1996.138
|View full text |Cite
|
Sign up to set email alerts
|

Attempted suicide and completed suicide in traumatic spinal cord injury. Case reports

Abstract: IntroductionFollow-up studies of spinal cord injury patients show a fourfold increase in the suicide rate. ! To examine this risk further we studied a consecutive series of 366 traumatic spinal cord injured patients from the time of their discharge from a spinal injuries unit, for a period of up to 8 years (mean 3.5 years). Attempted suicide had been the cause of the spinal injury in 11 patients (3%).The number of observed deaths was compared with the number expected. Expected deaths for all causes, suicide (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 1 publication
1
5
0
Order By: Relevance
“…First, a high percentage of people with SCI have sustained their injury through attempted suicide, for which the majority of the sample has been reported to have MHD. 2 This supports the relationship between the presence of an MHD and the incident of suicide attempt.…”
Section: Introductionsupporting
confidence: 68%
“…First, a high percentage of people with SCI have sustained their injury through attempted suicide, for which the majority of the sample has been reported to have MHD. 2 This supports the relationship between the presence of an MHD and the incident of suicide attempt.…”
Section: Introductionsupporting
confidence: 68%
“…Babidge et al (2001) reported that men with schizophrenia committed suicide at significantly younger ages (in their twenties) than those without schizophrenia. However, other studies have reported equal rates (Modestin et al, 1992;Harris et al, 1996).…”
Section: Introductionmentioning
confidence: 88%
“…The majority of people with SCI suffer from devastating chronic neuropathic pain syndromes that are so severe that depression, drug abuse and suicide often result (Cairnes et al, 1996; Harris et al, 1996; McKinley et al, 1999). SCI produces dramatic alterations in synaptic circuits relaying somatotopic sensory transmission in the dorsal horn.…”
Section: Glial Activation On Central Neuropathic Pain Following Scimentioning
confidence: 99%